A cryptic new species of hummingbird of the Campylopterus largipennis complex (Aves: Trochilidae) - Lopes, Leonardo Esteves; Vasconcelos, Marcelo Ferreira De; Gonzaga, Luiz Pedreira (Zootaxa, 2017)
A new species of Campylopterus sabrewing is described from eastern Brazilian tropical dry forests occurring below 900 m asl. Its holotype (MZUSP 99024) is an adult female from Sítio Duboca (16°43’19’’S, 43°58’20’’W, elevation 840 m), municipality of Montes Claros, state of Minas Gerais. A taxonomic revision based on more than 1,000 museum specimens revealed that the new taxon, together with C. largipennis, C. diamantinensis and C. obscurus (with C. aequatorialis considered as a subjective junior synonym) should be ranked as species. We provide a key to permit easy identification of the four species. The new species is very similar to the parapatric C. diamantinensis of high altitude “campos rupestres” above 1,000 m asl, differing from it by its smaller size and longer light tail tips, as well as by sternum measurements. Given the several threats faced by the habitat to which the new species is endemic, we propose to consider it as Vulnerable under the IUCN criteria.